CIVIL WAR IN CHECHNIA:POLITICAL FAILURE AND STRATEGIC RESPONSE - Bruce WARE, Robert (CENTRAL ASIA AND THE CAUCASUS, 2004)
over the last 15 years, Chechnia’s history has been a series of political failures. The last two of these failures, which occurred in 2003, have ushered in a civil war and are currently reflected in the shifting tactics of the conflict. For years to come, they will be played out in terms of personal suffering, regional instability, and geostrategic response. The recent political failure in Chechnia began with the structure of the government that was ratified in the constitutional referendum held in March 2003. The resulting presidential system is incompatible with the chronic fragmentation of Chechen society, particularly along the traditional lines of Chechnia’s 160-some teips, or clans. An individual executive inevitably will benefit some groups over others. In a political society as deeply and elaborately divided as that of Chechnia this can only exacerbate cleavages and increase political alienation. Instead of a presidential system, Chechnia need-ed some variety of consociational institutions, such as those that helped to stabilize the neighboring Republic of Daghestan from 26 July 1994 until a presidential system was imposed there on 26 July, 2003.